New strategies for the prevention of respiratory syncytial virus (RSV). (November 2022) - Messina, Alessandro; Germano, Chiara; Avellis, Vincenzo; Tavella, Elena; Dodaro, Valentina; Massaro, Alessio; Vitale, Raffaele; Masturzo, Bianca; Manzoni, Paolo
Abstract: Respiratory Syncytial Virus (RSV) is the main cause of lower respiratory tract infections (LRTIs) in newborns in the first two years of life. RSV disease has a traditional seasonal trend, with an onset and offset, duration and peak. Prematurity, male gender, bronchopulmonary dysplasia (BPD), critical congenital cardiovascular disorders (CCHD), neuromuscular diseases, congenital and inherited airways anatomical anomalies are the main risk factors for increased severity of this infection. RSV infection is associated with negative long-term respiratory outcomes, with excess of morbidity, resulting in reduced quality of life of the infected children and representing a burden for the healthcare costs and resources. Despite all the efforts, prevention remains, to date, the most effective strategy to reduce RSV-related morbidity. Among the current prevention strategies, strict hygiene, breastfeeding and passive immunization with the monoclonal antibody Palivizumab are the cornerstone. In the next future, it is likely that new possibilities of prevention will add, including use of more potent and longer-acting monoclonal antibodies, implementation of maternal vaccination in pregnancy, and active immunization in children. The purpose of this review is to provide an overview of the main current and future prevention strategies against RSV. Highlights: RSV remains one of the most important causes of hospitalization, morbidity and mortality in early infancy. Prevention remains, to date, the most effective strategy against RSV. Hygiene, breastfeeding and passive immunization using Palivizumab are the major, currently available prevention strategies. In the near future, long-acting monoclonal antibodies and maternal vaccination in pregnancy will play an important role.